Rehabilitasi Pasca Tambang Andesit Di Kabupaten Mempawah - Zhafran, Muhammad Farras; Akbar, Aji Ali; Jati, Dian Rahayu (Universitas Tanjungpura, 2023)
Peniraman Village, which is located in Sui Pinyuh District, Mempawah Regency, is a suitable area for andesite mining. The existence of PT. Sulenco Wibawa Perkasa, which is an andesite mining company that operates in Peniraman Village, allows for hazards and risks to the environment. This study aims to find out (1) What are the hazards and risks due to mining activities on environmental pollution, and (2) how efforts to control the hazards and risks from mining activities based on the SWOT analysis method. The method used in this study is quantitative-qualitative (Mix methods) which is presented with a descriptive method using the application of SWOT analysis. Data was collected from primary and secondary data, primary data was obtained from interviews, observation, and documentation while secondary data was obtained from supporting literature, government regulation No 22 of 2021, and UKL-UPL. The results of the analysis show that mining activities at PT. Sulenco Biwaba Perkasa still uses traditional tools. Impacts that have the potential to occur due to mining activities in the form of air pollution due to material mobilization, construction of supporting facilities and infrastructure, damage to primary road access due to transportation activities, and contamination of surface water due to land clearing and mining operations